FAMILIY'S SUPPORT AND ITS EFFECT IN INCREASING THE ELDERLY VISITATION TO POSYANDU - Wenty Ika Ariani; Nina Rahmadiliyani; Widyawati Widyawati (Proceedings of the International Conference on Applied Science and Health, 2017)
Introduction: Along with global tendency of increasing life expectancy, the number of elderly in Indonesia also tends to increase. To monitor the well-being of the elderly, both from the mental and the physical standpoints, the government-run integrated health service posts (Posyandu) hold a special program for the senior citizens. Aims: To analyze the association between families support and elderly visitation in Danau Panggang Health Center. Methods: This study used analytic survey with cross sectional design. The population were 378 elderly age 59 years old and older in Danau Panggang Health Center in 2015, and with Taro Yamane, the chosen sample was 194 elderly. The chi-square test was used for statistical analyses. Results: The study showed most of the respondents (56.7%) do not support and a majority of elderly do not actively participate (57.2%). Hypothesis test results showed that there is a correlation between family support and elderly participation to Posyandu with p-value = 0.000 < (α = 0.05). Conclusion: Family supports can increase elderly visitation to Posyandu. Participating in Posyandu activities and following the health officers’ directions prove beneficial to improve health conditions among the elderly. This research is expected to be an input for Posyandu to enhance its elderly program by optimizing the performance and presence of cadres in each activity.